THE ROLE OF IMMUNOLOGICAL RESEARCH IN THE HEALTHCARE SYSTEM OF UZBEKISTAN - Sharipova Postumiya Anvarovna; Mirzaaxmedova Nilufar Askarovna; Shagulyamova Kamola Lutfullaevna (Modern American Journals, 2025)
Modern medicine is increasingly paying attention to the human immune system, as it plays a key role in maintaining health and protecting the body from infectious, autoimmune, tumor, and allergic diseases. Immunological studies allow us to identify primary and secondary immunodeficiency states, allergic, autoimmune and inflammatory processes.
Keywords: immunology, patients, immune status, immunoglobulins, cytokines, Uzbekistan.